GENEALOGI WACANA PADA PESAN AGITATIF PIDATO PRABOWO SUBIYANTO TENTANG NKRI BUBAR TAHUN 2030 - Cosmas Gatot Haryono (Universitas Bunda Mulia, 2019)
ABSTRACTThe 2019 presidential election (Pilpres) is a very hot political battle compared to the 2014 election. The temperature of national politics has begun to heat up starting several months before the official campaign period set by the KPU. The